Genomic Analyses Reveal Evidence of Independent Evolution, Demographic History, and Extreme Environment Adaptation of Tibetan Plateau Agaricus bisporus - Sun, Lei; Fu, Yuhua; Yang, Yang; Wang, Xinxin; Cui, Weijie; Li, Dan; Yuan, Xiaohui; Zhang, Zhiwu; Fu, Yongping; Li, Yu (Frontiers in Microbiology, 2019)
Agaricus bisporus distributed in the Tibetan Plateau of China has high stress resistance that is valuable for breeding improvements. However, its evolutionary history, specialization, and adaptation to the extreme Tibetan environment are largely unknown. Here, we performed de novo genome sequencing of a representative Tibetan wild strain ABM and comparative genomic analysis with the reported European strain H97 and H39. The assembled ABM genome was 30.4 Mb in size, and comprised 8,562 protein-coding genes. The ABM genome shared highly conserved syntenic blocks and a few inversions with H97 and H39. The phylogenetic tree constructed by 1,276 single-copy orthologous genes in nine fungal species showed that the Tibetan and European A. bisporus diverged ~5.5 million years ago. Population genomic analysis using genome resequencing of 29 strains revealed that the Tibetan population underwent significant differentiation from the European and American populations and evolved independently, and the globe climate changes critically shaped the demographic history of the Tibetan population. Moreover, we identified key genes that are related to the cell wall and membrane system, and the development and defense systems regulated A. bisporus adapting to the harsh Tibetan environment. These findings highlight the value of genomic data in assessing the evolution and adaptation of mushrooms and will enhance future genetic improvements of A. bisporus.